Manajemen pengembangan sumber daya manusia di MAB Al-Amanah - Nisak, Choirotun; Wahyuni, Akhtim (LPPM Universitas Ibn Khaldun, Bogor, 2024)
This research aims to determine the planning, recruitment, and development of human resources at Bilingual Madrasah Aliyah. This research uses descriptive research methods with a phenomenological approach. The research object is located at the Bilingual Aliyah Madrasah in Junwangi village, Krian sub-district, Sidoarjo. The data collection techniques the researcher uses are through interviews, observation, and documentation. The data analysis technique is in three stages: data reduction, data presentation, and drawing conclusions. The results of this research show that Bilingual Madrasah Aliyah in human resource development management goes through three stages, namely: HR planning by holding meetings twice a year at the beginning of each semester, recruitment of competent human resources by the recruitment team with several requirements and written and unwritten tests in the form of interviews and microteaching, and HR development through training, assignments, and HR upgrading. Human resource development management at Bilingual Madrasah Aliyah has been carried out well, as evidenced by the increasing number of madrasah students every year; apart from that, the madrasah is also well known by the wider community. AbstrakTujuan penelitian ini untuk mengetahui perencanaan, rekrutmen, dan pengembangan sumber daya manusia di Madrasah Aliyah Bilingual (MAB). Penelitian ini menggunakan metode penelitian kualitatif deskriptif dengan pendekatan fenomenologi. Objek penelitian terletak di MAB, di desa junwangi, kecamatan Krian, Sidoarjo. Teknik pengumpulan data yang digunakan peneliti yaitu melalui wawancara, observasi, dan dokumentasi. Teknis analisis data yang digunakan ada tiga tahap yaitu: reduksi data, sajian data, dan penarikan kesimpulan. Hasil dari penelitian ini menunjukkan bahwa MAB dalam manajemen pengembangan sumber daya manusia melalui tiga tahapan yaitu: perencanaan SDM dengan mengadakan rapat dua kali dalam setahun di setiap awal semester, rekrutmen SDM yang kompeten oleh tim rekrutmen dengan beberapa persyaratan dan tes tertulis maupun tidak tertulis berupa wawancara serta microteaching, dan pengembangan SDM melalui pelatihan, penugasan, dan upgrading SDM. Manajemen pengembangan SDM di MAB sudah terlaksana dengan baik dibuktikan dengan meningkatnya jumlah siswa madrasah setiap tahun, selain itu madrasah juga dikenal oleh masyarakat luas.